New laws passed in Madagascar and Benin to enhance capacity to adapt to climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
New laws were passed in Benin and Madagascar to implement the Plant Treaty and Nagoya Protocol. The laws were drafted by national teams supported by a CCAFS project, drawing on CCAFS' science: that 1) demonstrated how to identify and access potentially adapted genetic materials of local food security crops negatively affected by climate change using the ITPGRFA and 2) analyzed options for national and community level implementation of the ITPGRFA and Nagoya Protocol.